Neuroprotection of multifunctional phytochemicals as novel therapeutic strategy for neurodegenerative disorders: antiapoptotic and antiamyloidogenic activities by modulation of cellular signal pathways. (15th February 2019) - Naoi, Makoto; Shamoto-Nagai, Masayo; Maruyama, Wakako
In neurodegenerative disorders, including Alzheimer's and Parkinson's disease, neuroprotection by diet and natural bioactive compounds has been proposed to prevent the onset and progress of neurodegeneration by modification of pathogenic factors. Plant food-derived phytochemicals protect neurons via targeting oxidative stress, mitochondrial dysfunction, neurotrophic factor deficit, apoptosis and abnormal protein accumulation. This review presents the molecular mechanism of neuroprotection by phytochemicals: direct regulation of mitochondrial apoptotic machinery, modification of cellular signal pathways, induction of antiapoptotic Bcl-2 protein family and prosurvival neurotrophic factors, such as brain- and glial cell line-derived neurotrophic factor, and prevention of protein aggregation. Multitargeted neuroprotective agents are under development based on the structure of blood–brain barrier-permeable phytochemicals to ameliorate brain dysfunction and prevent neurodegeneration.